Impact of grass cover management with herbicides on biodiversity, soil cover and humidity in olive groves in the Southern Iberian - Piñar Fuentes, J.C. (2021)
In the present work, we studied the effect of herbicide use on extensive olive grove cultivation. To carry out this study, we analysed the effect that herbicide use had on biodiversity, vegetation cover and soil water content. For this purpose, 96 vegetation and soil sampling points were first taken, then georeferenced, and for each sampling point, several bioclimatic variables were interpolated. We concluded that the management of cover crops with herbicides over a long period of time resulted in a decrease in biodiversity, and the dominance of some species that were more resistant to herbicides was increased. Another finding was that the vegetation cover was reduced in the resampling in cases with herbicide management and that the location within the cropland (under the tree canopy, road, boundary or pasture) also has an influence. Finally, the study of soil moisture shows that soil water content was lower in the case of management with herbicides than in the case of management without herbicides. This loss of soil moisture was more accentuated and faster in areas with less vegetation cover. This work highlights the need to change the management models for tree crops in order to preserve biodiversity, soil quality and optimise water resources in a context of accelerated climate change in one of the regions most severely affected by global warming, the Mediterranean belt.